Paradigma Islam dalam kewajiban menuntut ilmu bagi anak berkebutuhan khusus - Parhan, Muhamad; Mulyana Abdullah; Ganjar Eka Subakti (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
Seeking knowledge is an obligation for every Muslim, both men and women, including children with special needs, without exception. Children with special needs who have limitations should also learn because the current phenomenon is that there are still many children with special needs who do not get the opportunity to receive education. Therefore, this research aims to see how Islam views the obligation to study for children with special needs. The method used in this research is a qualitative method, which will produce some descriptive data. The data collection technique used is a literature study where the sources obtained come from books, journals, articles, and the al-Quran and Hadith. This research shows that by learning, children with special needs can continue their lives as independent human beings and become servants of Allah who are devout and have noble character.